Urinary brush border enzymes for early diagnosis of tubular dysfunction in patients with type 2 diabetes mellitus - T., Sasikala; Bitla, Aparna R.; Sachan, Alok (International Journal of Research in Medical Sciences, 2019)
Background: Diabetic nephropathy is a major cause of premature morbidity and mortality in type 1 and type 2 diabetes mellitus (T2DM) and hence new markers with better sensitivities are being investigated. The study was taken up to investigate whether urinary activities of N-acetyl-β-D-glycosaminidase (NAG), alkaline phosphatase (ALP), lactate dehydrogenase LDH) and Gamma glutamyl transferase (γ-GT) can be used as screening markers of renal dysfunction in patients suffering from T2DM. Methods: One hundred and four patients with T2DM along with 30 age- and gender-matched healthy individuals were included in the study. Patients were divided into three groups based on their u-MA levels i.e. normoalbuminuric (group1), micro albuminuric (group 2) and macroalbuminuric (group 3). Results: Urinary enzymes activity was significantly higher in patients with T2DM compared to controls (p<0.05). NAG, ALP, LDH, and GGT were significantly higher in group 3 compared to group1 and group 2 (p<0.0001). NAG, ALP, LDH and GGT showed significant positive correlation with MA (p=0.0001, r=0.308; p=0.0001, r=0.369; p=0.002, r=0.304, p=0.044, r=0.202 respectively). GGT and LDH showed highest sensitivity (86.21%, 84.00% respectively) and specificity (78.57%,53.49% respectively) for diagnosing renal dysfunction in patients with normoalbuminuria. Conclusions: The study suggests that u-GGT and LDH can be useful markers for assessing renal dysfunction in T2DM patients even before microalbuminuria manifests.